Habitual Snoring at Age 3 Years: Links with Parent-Rated Remembering in Daily Life and Academic Achievement at Age 7 Years. Issue 2 (February 2018) - Luo, Rebekah; Galland, Barbara C.; Gill, Amelia I.; Dawes, Patrick; Schaughency, Elizabeth
ABSTRACT: Objective: Habitual snoring in school-aged children is well known to link with poorer cognitive functioning and academic performance, but few studies have explored later developmental outcomes related to snoring initiated in early childhood. The aims of this study were to examine whether habitual snoring at age 3 years predicted perceived memory and academic functioning at age 7 years. Methods: Parents (n = 460) of children aged 7 years 2 ± 5 months completed a community follow-up survey about their perceptions of their child's sleep and health, memory in daily activities, and academic performance relevant to numeracy and literacy skills. The first survey was completed by 839 parents 4 years prior when children were aged 3 years (54.8% response rate at age 7 years). Parents rated their child's academic performance twice. First, they rated performance based on teachers' feedback relative to national standard ratings for numeracy and literacy, and second, based on their own observations. Results: Children reported to snore habitually at age 3 years received lower memory and academic composite score ratings at age 7 years. Age 3 years habitual snoring history predicted small but significant unique variation in age 7 years memory ( p = 0.005), literacy ( p < 0.001), and overall achievement ratings ( p = 0.016) in regressions controlling for covariates, with evidence suggesting that memory may mediate links between snoring history and academic performance. Conclusion: The findings suggest that habitual snoring in early childhood may adversely affect success in beginning schooling. More research is still needed to determine the best time for treatment so that longer-term consequences of sleep-disordered breathing may be prevented.